Akadеmik litsеylar o‗quv jarayonida mobil tеxnologiyalaridan foydadanishning ba‘zi masalalari (SCIENCE and SOCIETY, 2023)
In the article, the author revealed some issues of achieving efficiency using mobile technologies in the educational process of academic lyceums.